Quantifying CDK inhibitor selectivity in live cells - Carrow I. Wells (Nature Portfolio, 2020)
Cyclin-dependent kinase (CDK) inhibitors are widely used both in the clinic and for basic research aimed at dissecting the specific cellular functions of specific CDKs. Here, the authors report the development of a panel of fluorescent reporter probes and provide a comprehensive profile of the inhibitory activity of several CDK inhibitors towards all 21 CDKs in living cells.